Museum Tsunami sebagai Sumber Belajar IPS di SMP Kota Banda Aceh - Fathia Irani; Hariyono Hariyono; Ari Sapto (Graduate School of Universitas Negeri Malang, 2018)
Aceh Tsunami Museum as something special and strategic as a learning resource in IPS learning has potential locally and relevant with some IPS materials at IPS level. The Tsunami Museum can include information on changes in the natural state due to tsunami events, population activity and population dynamics that occur after the tsunami. The chosen learning approach should be a more portable approach of engaging more students in learning, learning materials and resources drawn from the immediate environment with students (contextual learning). The purpose of this research is to describe deeply the utilization of Tsunami Museum in IPS teaching and learning process at SMP Kota Banda Aceh. This research uses approach and type of qualitative research descriptive. The results showed that the implementation of IPS learning by utilizing the Tsunami Museum as a learning resource has been implemented although not maximal, this is because, the level of competence of teachers to various IPS learning resources. Furthermore, the potential of Tsunami Museum is available to support IPS learning process. Implementation of IPS learning by utilizing the Tsunami Museum is done by the method of visit (study tour).Museum Tsunami Aceh sebagai sesuatu yang khusus dan strategis memiliki potensi sebagai sumber pembelajaran IPS. Museum Tsunami memuat informasi mengenai perubahan keadaan alam akibat kejadian tsunami, aktivitas penduduk serta dinamika kependudukan yang terjadi setelah tsunami. Pendekatan pembelajaran kontekstual memberikan porsi keterlibatan siswa dalam belajar, materi dan sumber belajar diambil dari lingkungan yang dekat dengan siswa. Tujuan dari penelitian ini adalah untuk mendeskripsikan secara mendalam pemanfaatan Museum Tsunami dalam proses belajar mengajar IPS di SMP Kota Banda Aceh. Penelitian ini menggunakan pendekatan dan jenis penelitian kualitatif deskriptif. Hasil penelitian menunjukkan bahwa pelaksanaan pembelajaran IPS dengan memanfaatkan Museum Tsunami sebagai sumber belajar sudah dilaksanakan walaupun belum maksimal, tingkat kompetensi guru terhadap berbagai sumber belajar IPS. Selanjutnya, potensi museum Tsunami tersedia untuk menunjang proses pembelajaran IPS. Pelaksanaan pembelajaran IPS dengan memanfaatkan Museum Tsunami dilakukan dengan metode kunjungan (study tour).